PRIORITIES AND PERSPECTIVES OF THE DEVELOPMENT OF THE NATIONAL RESEARCH UNIVERSITY - Anatoly A. Tashkinov; Vasily Yu. Petrov; Vladimir I. Makarevich (Высшее образование в России)
The article presents the results of the first stage of functioning of Perm Polytechnic University as anational research university in conditions of state support. Priority directions and spheres of NRU activity have been marked out. The goals and perspectives of university development have been outlined. The university develops its activities based on the unity of educational, scientific and innovational processes, participates in formation of a global education and research space, provides training for a new generation specialists adapted to socio-cultural conditions of Russia and first-rate countries, contributes to the success of its graduates in competitive environments.